Immediate Effects of Transcranial Direct Current Stimulation on Obsession-Induced Anxiety in Refractory Obsessive-Compulsive Disorder: A Pilot Study. Issue 4 (December 2018) - Todder, Doron; Gershi, Adi; Perry, Zvi; Kaplan, Zeev; Levine, Joseph; Avirame, Keren
Abstract : Objective: Studies have shown that transcranial direct current stimulation (tDCS) has immediate effects on brain activity. The aim of this study was to investigate the potential use of tDCS to regulate obsession-induced anxiety immediately after symptom provocation in patients with refractory obsessive-compulsive disorder (OCD). Methods: Twelve patients with refractory OCD received cathode, anode, and sham transcranial direct current stimulation over the medial prefrontal cortex conjugant to pharmacological treatment in a crossover design. Before and after the DC stimulation, patients graded the intensity of their anxiety after a short exposure to a provoking stimulus using the visual analogue scale. Clinical questionnaires assessing symptoms severity were also applied before each stimulation mode. Results: We found a statistically significant decrease in the severity of the obsession-induced anxiety (decreased visual analogue scale) as a result of cathode tDCS in comparison with the anode and sham stimulation. Reduction in obsession-induced anxiety was consistent, yet short lasting, and was independent of symptom severity. Conclusions: Cathode tDCS could be potentially used to regulate obsession-induced anxiety in refractory OCD patients. Further studies are warranted to confirm our results as well as to determine whether tDCS can achieve prolonged benefits in OCD and be of aid in behavioral treatments based on exposure.